Human Papillomavirus (HPV) Infection and The Spectrum of Diseases It Causes: A Literature Review - Hanifah, Hanum Retno; Hapsari, Yunita; Wardana, Shira Putri; Haikal, Muhammad (Jurnal Biologi Tropis, 2025)
Human Papillomavirus (HPV) is a sexually transmitted infection (STI) pathogen that plays a significant role in the development of benign and malignant diseases. This study used a literature review of national and international articles (2015–2025) obtained through Google Scholar, PubMed, and accredited journals. HPV is classified into high-risk types associated with cancer (primarily HPV 16 and 18) and low-risk types that commonly cause genital warts. Initial infection is often asymptomatic, but persistent infection can lead to cell transformation due to the activity of the oncoproteins E6 and E7. Globally, HPV prevalence remains high, with regional variations and a strong association with low vaccination coverage. Management includes pharmacological therapy, surgery, and a combination of chemotherapy and radiotherapy. While the primary prevention strategy is HPV vaccination (bivalent, quadrivalent, and nonavalent), which is currently being expanded to primary school-aged girls in Indonesia. Recent developments include new-generation therapeutic vaccines (Vvax001, PANHPVAX) that promise broader protection. It can be concluded that primary vaccination remains the most effective strategy to reduce the burden of disease caused by HPV, so that increased immunization coverage, public education, and further research related to new generation vaccines are needed.